2019
DOI: 10.1016/j.pmedr.2019.100991
|View full text |Cite|
|
Sign up to set email alerts
|

Associations of weight cycling with cardiovascular health using American Heart Association’s Life’s Simple 7 in a diverse sample of women

Abstract: HighlightsMost women reported history of weight cycling (range: 0–20 episodes).Any history of weight cycling was associated with poorer cardiovascular health.Associations were stronger in pre-menopausal and women with no pregnancy history.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 31 publications
1
16
0
Order By: Relevance
“…83 Together, these results suggest that while weight out of 19 publications showed a positive correlation between weight cycling and increased body fat and deposition of AT centrally but did not find a correlation with increased risk of T2DM. Many other studies have seen a correlation between weight cycling and worsened cardiometabolic disease, atherosclerosis, and even mortality, [88][89][90][91] suggesting that it is still an important area of study.…”
Section: Wei G Ht Lossmentioning
confidence: 99%
“…83 Together, these results suggest that while weight out of 19 publications showed a positive correlation between weight cycling and increased body fat and deposition of AT centrally but did not find a correlation with increased risk of T2DM. Many other studies have seen a correlation between weight cycling and worsened cardiometabolic disease, atherosclerosis, and even mortality, [88][89][90][91] suggesting that it is still an important area of study.…”
Section: Wei G Ht Lossmentioning
confidence: 99%
“…Despite these limitations, our study also has pertinent strengths, particularly because of its large sample size and use of both semiquantitative and quantitative outcomes. Moreover, although the effects of weight cycling on a variety of outcomes, including cardiac disease and diabetes (8,9), have been studied, this is the first investigation, to our knowledge, of the effects of weight cycling on knee joint degeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Although the effects of weight cycling on obesity‐related diseases, including mortality, cardiovascular disease, type 2 diabetes, body composition, and cancer, have been explored, with some studies reporting no effects and others citing increased risks (8,9), the effects of weight cycling on OA have not been thoroughly investigated. However, the effects of weight loss and obesity on OA are well studied, and it has been shown that weight loss can prevent the onset of OA, improve symptoms and function, and increase quality of life (5).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Weight cycle may contribute to cardiovascular disease risk by leading to visceral fat or pervascular adipose tissue, which are more strongly associated with cardiovascular disease risk. The biological mechanisms behind preferential fat deposition are not fully elucidated in humans, but the repeated overshoot theory is also proposed to explain how weight cycling may increase cardiovascular disease risk (Byun, Bello, Liao, Makarem & Aggarwal, 2019). Generally, in the case of weight regain, muscle mass increases less, while body fat increases more (Galal et al, 2008).…”
Section: Discussionmentioning
confidence: 99%